Newly developed pseudogout arthritis after therapy with MAGE-A4 directed TCR T cells responded to treatment with tocilizumab. Issue 7 (7th July 2021) - Kim, Sang T.; Tayar, Jean; Fu, Siqing; Ke, Danxia; Norry, Elliot; Sun, Amy; Miller, Juli; Hong, David S.
Abstract : With durable cancer responses, genetically modified cell therapies are being implemented in various cancers. However, these immune effector cell therapies can cause toxicities, including cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome (ICANS). Pseudogout arthritis is an inflammatory arthritis induced by deposition of calcium pyrophosphate dihydrate crystals. Here, we report a case of pseudogout arthritis in a patient treated with MAGE-A4 directed T cell receptor T cells, for fallopian tube cancer. The patient developed CRS and ICANS 7 days after infusion of the T cells. Concurrently, the patient newly developed sudden onset of left knee arthritis. Synovial fluid analyses revealed the presence of calcium pyrophosphate dihydrate crystal. Notably, the pseudogout arthritis was resolved with tocilizumab, which was administered for the treatment of CRS and ICANS. Immunoprofiling of the synovial fluid showed that the proportion of inflammatory interleukin 17 (IL-17)-producing CD4 + T (Th17) cells and amount of IL-6 were notably increased, suggesting a potential role of Th17 cells in pseudogout arthritis after T-cell therapy. To the best of our knowledge, this is the first reported case of pseudogout arthritis after cell therapy. Clinicians, especially hematologists, oncologists and rheumatologists, should be aware that pseudogout arthritis can be associated with CRS/ICANS.